DESCRIPTION OF THE DEVELOPMENT OF LOCAL WISDOM BASED SCHOOL CULTURE IN THE EXCELLENT JUNIOR HIGH SCHOOL - Abd. Qadir Muslim; Akhmad Nurul Kawakip (Erudio Journal of Educational Innovation, 2022)
This research aims to describe and find the development of local wisdom based school culture in the Excellent Junior High School. The research design used a qualitative approach. The data collection used interview and observation techniques. The research results showed that the development of local wisdom based school culture in the Excellent Junior High Shcool was significant in term of quantity and quality. The description of the research was by applying some habits such as 5S (Sapa/Greet, Senyum/Smile, Salam/Regard, Sopan and Santun/Polite), nationalism culture (singing Indonesian anthem), literacy culture, clean culture, speaking the local language on Friday, and religious culture. Such habituation was done through some steps such as: giving the idea, clarification, socialization, implementation, and evaluation. An excellent school is a school that applies the local wisdom based school culture since it can give positive values for the students such as raising the value of discipline, politeness, good deed, being committed to the God, smartness, hospitality, cooperation, integrity, and independence. Such habituation can improve the quality of the school and create the academic and non-academic achievement. The proof was the research result as applied in the Excellent Junior High Schools. The schools reached the title of national adiwiyata, became the reference school and pilot project of character education. The conclusion is the local wisdom based school culture implemented consistently can be one of the indicators to be an excellent school in the society